Assessment of MATLAB Algorithm used for LVEF Quantification for SPECT and MRI Images - Musa, Mahmoud A. A.; Zobly, Sulieman M. S.; Ahmed, Mawahib G. A. (Gezira Journal of Engineering and Applied Sciences; مجلد 20 عدد 2 (2025), 2026)
Accurate quantification of left ventricular ejection fraction (LVEF) from gated single photon emission computed tomography (SPECT) is essential for cardiac function assessment and treatment planning. However, commercial software such as QGS and 4D-MSPECT are expensive and inaccessible in many low-resource centers. This study aimed to develop and validate a semi-automated MATLAB algorithm for LVEF quantification from SPECT images, using cardiac magnetic resonance imaging (CMRI) as the gold standard reference. The study was conducted on 12 patients with suspected coronary artery disease [mean age 58.3 ± 9.7 years; 7 males and 5 females]. All patients underwent same-day gated SPECT and CMRI after ethical approval from the University of Gezira Institutional Review Board. SPECT images were reconstructed using a Hanning filter, then denoised using a 3D Gaussian filter. The left ventricle was segmented semi-automatically using the `activecontour` function, and end-diastolic counts (EDC) and end-systolic counts (ESC) were extracted using `regionprops` to calculate LVEF with the equation: [(EDC-ESC)/EDC] × 100. Performance was evaluated using Pearson correlation, ICC, and Bland-Altman analysis compared to CMRI by Simpson’s method. Mean LVEF by MATLAB was 44.8 ± 16.2% vs 52.3 ± 16.8% by CMRI, with strong correlation r=0.94 and ICC=0.93. Sensitivity for detecting LVEF<50% was 85.7% and specificity was 100%. The algorithm provides an accurate and low-cost alternative to measure LVEF, with the need for larger multi-center studies. تمثل أمراض القلب والأوعية الدموية عبئاً صحياً عالمياً كبيراً، وفي السودان تزايدت الإصابة بها في السنوات الأخيرة جزئياً بسبب عدم دقة التشخيص في تصوير القلب وارتفاع تكلفة البرامج التجارية لمعالجة الصور. يعتبر القياس الدقيق لكسر قذف البطين الأيسر (LVEF) ضرورياً لتقييم وظيفة القلب. هدفت هذه الدراسة إلى تطوير والتحقق من خوارزمية تعتمد على MATLAB ومنخفضة التكلفة للحساب الآلي لـ LVEF من صور التصوير المقطعي المحوسب بانبعاث الفوتون المفرد المبوّب (Gated SPECT). خضع 12 مريض قلب لتصوير Gated SPECT، وتم تطوير صندوق أدوات MATLAB مخصص لإجراء تجزئة البطين الأيسر وكشف عدّات نهاية الانبساط (EDC) وعدّات نهاية الانقباض (ESC) وحساب LVEF. تم تقييم أداء الخوارزمية بمقارنة قيم LVEF المحسوبة مع القيم المرجعية وتقييم الدقة التشخيصية. من بين 12 مريض، أظهر 5 مرضى وظيفة قلب طبيعية بقيم LVEF: 60.4%، 55.8%، 53.4%، 56.3%، و 59.1% بدقة 97% مقارنة بالبرنامج المرجعي، بينما أظهر 7 مرضى ضعفاً في الوظيفة بقيم LVEF: 38.5%، 34.5%، 25.3%، 36.1%، 18.8%، 20.0%، و 40.7%. أعطى تحليل الارتباط معامل ارتباط 0.80= r . تخلص الدراسة إلى أن خوارزمية MATLAB المقترحة توفر قياساً دقيقاً ومتاحاً وقابلاً للتكرار لـ LVEF من صور Gated SPECT، مما يقدم بديلاً عملياً للبرامج التجارية باهظة الثمن. اوصي بدمج هذه الطريقة في التحليل الروتيني لـ SPECT في المراكز ذات الموارد المحدودة والتحقق منها على عينة أكبر.